Scratching the Surface (Modification) Developing a Quantitative Liquid Chromatography-Tandem Mass Spectrometry Method for the Investigation of PEGylated and Non-PEGylated Lipid Mixtures on Lipid-Coated Lanthanide Nanoparticles - Arnett, Loryn P (Langmuir : the ACS journal of surfaces and colloids, 2021)
We are interested in developing lanthanide nanoparticles (LnNPs) of the general formula NaLnF4 as high-sensitivity reagents for mass cytometry. These LnNPs must be coated to provide colloidal stability in aqueous buffer and functionality for detecting cellular biomarkers. Lipid bilayer coatings are a promising approach, but one requires an analytical technique to enable characterization of the NP coating composition as opposed to the composition of the lipid formulation used in the coating process. However, quantification of the lipid composition of lipid coatings on polymer and inorganic NPs is not common practice in the field. Here we describe a method based on high-performance liquid chromatography (LC) for separations and triple quadrupole tandem mass spectrometry (MS/MS) instrumentation for detection and show that it can quantify complex lipid mixtures using small (<1 μg) amounts of sample. Our lipid formulation consisted of a mixture of egg sphingomyelin, 1,2-dioleoyl-sn-glycero-3-phosphocholine, 1,2-dioleoyl-3-trimethylammonium-propane, cholesterol-PEG600, and 1,2-distearoyl-sn-glycero-3-phosphoethanolamine-N-[biotinyl(polyethylene glycol)-2000]. We were able to extract the coating from lipid-coated 35 nm diameter LnNPs, quantify the lipid/NP ratio, and show that the coating composition differed from the composition of the lipid formulation for several of the species. Knowledge of the actual composition of the lipid coating for lipid-coated NPs is critical for designing and optimizing application of these materials. Our results establish the value of LC-MS/MS characterization of lipid-coated NPs, thus providing an important new addition to the toolbox available for characterizing these types of nanomaterials